Impact of infection with human immunodeficiency virus-1 (HIV) on the risk of cancer among children in Malawi - preliminary findings - Mutalima, Nora (BioMed Central, 2010)
BACKGROUND: The impact of infection with HIV on the risk of cancer in children is uncertain, particularly for those living in sub-Saharan Africa. In an ongoing study in a paediatric oncology centre in Malawi, children (aged ≤ 15 years) with known or suspected cancers are being recruited and tested for HIV and their mothers or carers interviewed. This study reports findings for children recruited between 2005 and 2008. METHODS: Only children with a cancer diagnosis were included. Odds ratios (OR) for being HIV positive were estimated for each cancer type (with adjustment for age (<5 years, ≥ 5 years) and sex) using children with other cancers and non-malignant conditions as a comparison group (excluding the known HIV-associated cancers, Kaposi sarcoma and lymphomas, as well as children with other haematological malignancies or with confirmed non-cancer diagnoses). RESULTS: Of the 586 children recruited, 541 (92%) met the inclusion criteria and 525 (97%) were tested for HIV. Overall HIV seroprevalence was 10%. Infection with HIV was associated with Kaposi sarcoma (29 cases; OR = 93.5, 95% CI 26.9 to 324.4) and with non-Burkitt, non-Hodgkin lymphoma (33 cases; OR = 4.4, 95% CI 1.1 to 17.9) but not with Burkitt lymphoma (269 cases; OR = 2.2, 95% CI 0.8 to 6.4). CONCLUSIONS: In this study, only Kaposi sarcoma and non-Burkitt, non-Hodgkin lymphoma were associated with HIV infection. The endemic form of Burkitt lymphoma, which is relatively frequent in Malawi, was not significantly associated with HIV. While the relatively small numbers of children with other cancers, together with possible limitations of diagnostic testing may limit our conclusions, the findings may suggest differences in the pathogenesis of HIV-related malignancies in different parts of the world.